Gene expression analysis reveals mir-29 as a linker regulatory molecule among rheumatoid arthritis, inflammatory bowel disease, and dementia: Insights from systems biology approach - Devi Soorya Narayana S.; Vino Sundararajan (PLoS ONE, 2025)
Background Rheumatoid arthritis (RA) is a degenerative autoimmune disease, often managed through symptomatic treatment. The co-occurrence of the reported extra-articular comorbidities such as inflammatory bowel disease (IBD), and dementia may complicate the pathology of the disease as well as the treatment strategies. Therefore, in our study, we aim to elucidate the key genes, and regulatory elements implicated in the progression and association of these diseases, thereby highlighting the linked potential therapeutic targets. Methodology Ten microarray datasets each for RA, and IBD, and nine datasets for dementia were obtained from Gene Expression Omnibus. We identified common differentially expressed genes (DEGs) and constructed a gene-gene interaction network. Subsequently, topology analysis for hub gene identification, cluster and functional enrichment, and regulatory network analysis were performed. The hub genes were then validated using independent microarray datasets from Gene Expression Omnibus. Results A total of 198 common DEGs were identified from which CD44, FN1, IGF1, COL1A2, and POSTN were identified as the hub genes in our study. These hub genes were mostly enriched in significant processes and pathways like tissue development, collagen binding, cell adhesion, regulation of ERK1/2 cascade, PI3K-AKT signaling, and cell surface receptor signaling. Key transcription factors TWIST2, CEBPA, EP300, HDAC1, HDAC2, NFKB1, RELA, TWIST1, and YY1 along with the miRNA hsa-miR-29 were found to regulate the expression of the hub genes significantly. Among these regulatory molecules, miR-29 emerged as a significant linker molecule, bridging the molecular mechanisms of RA, IBD, and dementia. Validation of our hub genes demonstrated a similar expression trend in the independent datasets used for our study. Conclusion Our study underscores the significant role of miR-29 in modulating the expression of hub genes and the associated transcription factors, which are crucial in the comorbidity status of RA, dementia, and IBD. This regulatory mechanism highlights miR-29 as a key player in the pathogenesis of these comorbid diseases.